Diversifying Internet delivery. - Carpenter, B.E.
In this paper the authors describe how users will be able to choose from several levels of performance-not one-size-fits-all-when a new service scheme replaces the Internet's existing infrastructure
Keywords: Internet delivery diversification; Internet infrastructure; Performance level; Service scheme replacement